Mitigating cadmium toxicity: Role of caffeine in the reduction of oxidative stress - Ahmed Aljazzar (Open Veterinary Journal)
Background: Cadmium is a common environmental pollutant that causes severe health issues. Many studies have proposed antioxidant foods to combat cadmium toxicity. One such antioxidant agent is caffeine, and hence, this study investigated its effects.